2011
DOI: 10.1021/nn202383b
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Gibbs Monolayers of DNA-Capped Nanoparticles at the Air–Liquid Interface

Abstract: Using grazing-incidence small-angle X-ray scattering in a special configuration (parallel SAXS, or parSAXS), we mapped the crystallization of DNA-capped nanoparticles across a sessile droplet, revealing the formation of crystalline Gibbs monolayers of DNA-capped nanoparticles at the air-liquid interface. We showed that the spatial crystallization can be regulated by adjusting both ionic strength and DNA sequence length and that a modified form of the Daoud-Cotton model could describe and predict the resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
73
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 45 publications
4
73
1
1
Order By: Relevance
“…We used parallel small-angle x-ray scattering (parSAXS) which enabled us to uniquely probe the ordering phenomenon at the air-water interface independent of substrate effects. [10] Notably, our system is fully equilibrated (free particle exchange between bulk solution and Gibbs layer) and friction-free (in liquid rather than on a solid substrate). A droplet of polyT-DNA-capped AuNPs was deposited in a sealed chamber with a reservoir at the same salt concentration, in order to maintain equilibrium vapor pressure in the chamber and thus to stabilize the droplet volume and minimize far-from-equilibrium drying effects (see the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used parallel small-angle x-ray scattering (parSAXS) which enabled us to uniquely probe the ordering phenomenon at the air-water interface independent of substrate effects. [10] Notably, our system is fully equilibrated (free particle exchange between bulk solution and Gibbs layer) and friction-free (in liquid rather than on a solid substrate). A droplet of polyT-DNA-capped AuNPs was deposited in a sealed chamber with a reservoir at the same salt concentration, in order to maintain equilibrium vapor pressure in the chamber and thus to stabilize the droplet volume and minimize far-from-equilibrium drying effects (see the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…A droplet of polyT-DNA-capped AuNPs was deposited in a sealed chamber with a reservoir at the same salt concentration, in order to maintain equilibrium vapor pressure in the chamber and thus to stabilize the droplet volume and minimize far-from-equilibrium drying effects (see the Supporting Information). [10] The scattering spectra at the interface of the droplet were captured in real time and in situ for non-base-pairing DNA-NPs across a range of ISs of monovalent NaCl and divalent MgCl 2 solutions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one approach, charged Langmuir monolayers have been used as templates that attract and crystallize capped nanoparticles from solutions [5][6][7]. In a different approach, it has been found that by manipulating salt concentrations in NPs suspensions, a Gibbs-like monolayer can be spontaneously formed and crystallized [8][9][10]. It should be emphasized that for all these assemblies, 2D or 3D, salts play a decisive role in tweaking the charge of the DNA strands and facilitate specific 3D assembly of NPs or migration of NPs to the liquid interface [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In a different approach, it has been found that by manipulating salt concentrations in NPs suspensions, a Gibbs-like monolayer can be spontaneously formed and crystallized [8][9][10]. It should be emphasized that for all these assemblies, 2D or 3D, salts play a decisive role in tweaking the charge of the DNA strands and facilitate specific 3D assembly of NPs or migration of NPs to the liquid interface [5][6][7][8][9][10]. In fact, a recent study suggests that the underlying mechanism that drives DNA-capped AuNPs to the surface and to crystallization has to do with the role of salt in tweaking the hydrophobic-hydrophilic character of the DNA-capped AuNPs [10].…”
Section: Introductionmentioning
confidence: 99%